Predictive Modeling of Cave Settlements In Karst Area of Kapuas Basin, West Kalimantan - Hafsari, Ni Luh Gde Dyah Mega; Kusmartono, Vida Pervaya Rusianti; Wibisono, M. Wishnu (Badan Riset dan Inovasi Nasional, 2023)
Starting in the 1970s, the captivating archaeological potency in the tropical rainforest area of West Kalimantan started to be revealed. Since then, several expeditions and research had been conducted by The National Research Center for Archaeology and Archaeology Office in South Kalimantan. One of them was an exploration and excavation led by Vida P.R. Kusmartono from 2013-2019. Previous studies have shown that the area of Upper Kapuas Basin possesses numerous archaeological resources, however, many of the areas remain uncovered. This condition is caused by the extensiveness and difficulty of this area to be reached. For that reason, in 2020, we created a predictive model to give an overview of the probability of archaeological caves in this area. This predictive model uses environmental variables and is based on the hypothesis of the environmental resources variables in choosing cave settlements in the prehistory era. The variables used are the elevation of the valley, the proximity distance from the water source, the steepness of the slope, the direction of the slope, and the lineament density. Analysis of the variable elevation of the valley, proximity distance from the water source, and the steepness of the slope produced a map of accessibility. This map was then integrated with the lineament density variable and considered the direction of the slope to produce a map of potential areas for cave settlements.